2019
DOI: 10.1186/s12862-019-1521-1
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally high rates of positive selection on the rbcL gene in the genus Ilex (Aquifoliaceae)

Abstract: BackgroundThe genus Ilex (Aquifoliaceae) has a near-cosmopolitan distribution in mesic habitats from tropical to temperate lowlands and in alpine forests. It has a high rate of hybridization and plastid capture, and comprises four geographically structured plastid groups. A previous study showed that the plastid rbcL gene, coding for the large subunit of Rubisco, has a particularly high rate of non-synonymous substitutions in Ilex, when compared with other plant lineages. This suggests a strong positive select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 55 publications
(99 reference statements)
1
17
0
Order By: Relevance
“…and reported positive selection in most land plants but not in algae and cyanobacteria. A similar study supported the positive selection of rbcL in Ilex using 240 Ilex sequences (Yao et al, 2019). Positive selection in the chloroplast genome, including at rbcL, has been reported in numerous plant taxa (Bock et al, 2014).…”
Section: Characterization Of Cp Genome and Genetic Variations In Arnesupporting
confidence: 71%
See 1 more Smart Citation
“…and reported positive selection in most land plants but not in algae and cyanobacteria. A similar study supported the positive selection of rbcL in Ilex using 240 Ilex sequences (Yao et al, 2019). Positive selection in the chloroplast genome, including at rbcL, has been reported in numerous plant taxa (Bock et al, 2014).…”
Section: Characterization Of Cp Genome and Genetic Variations In Arnesupporting
confidence: 71%
“…Most genes in the Boraginaceae exhibited stable gene evolution (purifying selection). Positive selection was detected in rbcL, a gene encoding the large subunit of Rubisco, which is commonly observed in angiosperm cp genomes due to the elevated selective pressure for this protein (Kapralov and Filatov, 2007;Shi et al, 2019;Yao et al, 2019). Large-scale studies confirmed that positive selection of rbcL is widespread among land plants.…”
Section: Characterization Of Cp Genome and Genetic Variations In Arnementioning
confidence: 85%
“…Positive selection for rbcL is widespread among land plants ( Kapralov & Filatov, 2007 ; Yao et al, 2019 ; Shen et al, 2020 ) and several studies have demonstrated that positive selection on specific amino-acids in rubisco is linked to plant adaptation to different environmental stresses, facilitating adaptive radiation into diverse ecological niches ( Hermida-Carrera et al, 2017 ). Examples include adaptations to dry or wet climates ( Kapralov & Filatov, 2006 ; Galmés et al, 2014 ), to high altitude environments ( Hu et al, 2015 ) and in transitions from C 3 to C 4 photosynthesis ( Christin et al, 2008 ; Kapralov, Smith & Filatov, 2012 ; Hermida-Carrera et al, 2020 ), including in Flaveria (Asteraceae, tribe Tageteae) ( Kapralov et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, it assists in comparative studies of population diversity of several plants (Hajibabaei et al, 2007). A high rate of a positive selection among different lineages in Ilex (Aquifoliaceae) was demonstrated (Yao et al, 2019). Amandita et al (2019) has shown that rbcL barcoding has a much higher level of sequence recoverability than matK (95% and 66%, respectively) which in turn have had a great ability to differentiate between flowering plants.…”
Section: Dna Barcoding Of M Sativa Rbcl and Rpoc1 And Its Phylogenetmentioning
confidence: 99%